"An extra layer of pressure to be my best self": Healthcare provider perspectives on how doulas foster accountability and bridge gaps in pregnancy-related care - Reiley Reed; Ashley Nguyen; Marna Armstead; Alli Cuentos; Marlee-I Mystic; Jennet Arcara; Andrea V. Jackson; Cassondra Marshall; Anu Manchikanti Gomez (Elsevier, 2023)
Despite the importance of respectful pregnancy care, birthing people experience high rates of mistreatment in clinical settings in the United States. In light of persistent racialized maternal and infant health inequities, doula care is increasingly promoted as an intervention. Limited research has examined healthcare providers' experiences with doulas.As part of an evaluation of community doula programs in San Francisco, California, we interviewed physicians (n ​= ​11), certified nurse-midwives (n ​= ​7), and nurses (n ​= ​10) who worked in hospitals and clinics where doula clients receive care. Using reflexive thematic analysis, we identified two themes around how providers perceive doulas to affect pregnancy-related care. First, providers described doulas fostering accountability at multiple levels. Providers described how their personal sense of accountability to patients increased in the presence of doulas; at times, this mitigated racism and implicit bias in clinical settings. Additionally, through the partnership between the community doula organization and local hospitals, doulas engaged in bidirectional feedback with providers, creating opportunities for institutional-level accountability. Second, providers perceived doulas to bridge gaps in care for pregnant and birthing people by providing services, such as continuous labor support, that are not realistic for clinicians to provide.This analysis contributes to the broader literature on doula care by describing mechanisms through which doulas improve pregnancy-related care. Doulas may be critical for birthing people who are most likely to experience mistreatment due to racism and other dimensions of oppression. Future research should explore facilitators and barriers to developing partnerships between clinical sites and doula organizations and the long-term effects of these partnerships on health equity.